Fluorescencní in situ hybridizace (FISH) v diagnostice dĕtských akutních lymfatických leukémií (ALL) - Zemanová, Z; Michalová, K; Brezinová, J; Sindelárová, L; Kurková, S; Smísek, P; Zuna, J; Trka, J; Starý, J (Casopis lekaru ceskych, 2001)
Classical cytogenetic analysis plays an important role in the diagnosis, classification, therapy monitoring and prognosis of patients with leukemia. Many recurrent cytogenetic abnormalities with major prognostic values have been described in childhood ALL. Hyperdiploidy and/or t(12;21) are associated with good prognosis, whereas t(9;22) and/or rearrangements of MLL gene correlate with poor outcome and therefore early detection of these abnormalities is very important. FISH can overcome some limitations of conventional cytogenetic and molecular-genetic analyses and due to high sensitivity specific chromosomal aberrations in mitoses and/or interphase nuclei can be detected. In the Center of Oncocytogenetics of the 3rd Medical Department for assessment of hyperdiploidy and structural rearrangements we use double-color FISH with centromeric and/or locus-specific probes and complex aberrations are ascertained by whole chromosome painting probes and multicolor FISH. Among 275 children with ALL examined during the last 8 years by different FISH methods we found seven patients with translocation t(9;22) and 14 patients with MLL rearrangements in bone marrow cells. Since 1988 we focus on detection of hyperdiploidy and/or t(12;21). High hyperdiploidy was found in 35 children, 10 of them had further complex rearrangements. Translocation t(12;21) was proved in 37 patients and complex rearrangements were found in 22 of them. FISH, cytogenetic and molecular-genetic analyses become obligatory for the first diagnostic examination as well as for monitoring of treatment effect in children with ALL.
Keywords: Proto-Oncogenes; Transcription Factors; genová přestavba; hybridizace in situ fluorescenční; Gene Rearrangement; Humans; transkripční faktory; Histone-Lysine N-Methyltransferase; In Situ Hybridization, Fluorescence; histonlysin-N-methyltransferasa; Myeloid-Lymphoid Leukemia Protein; ploidie; DNA-Binding Proteins; protoonkogeny; protoonkogenní protein MLL; Translocation, Genetic; Precursor Cell Lymphoblastic Leukemia-Lymphoma; DNA vazebné proteiny; translokace genetická; akutní lymfatická leukemie; lidé; dítě; Child; Ploidies